Smart Traffic Management Systems: A Comprehensive Review of Existing Solutions - Siddhant Dawkhare; Amrish Jadhav; Yash Jariwala; Palak Desai (International Journal of Optical Innovations & Research, 2024)
In our nation today, when the number of automobiles keeps growing faster than the resources at our disposal, managing this problem is getting harder, and things get worse when accidents happen. Numerous facets of society are impacted by this issue, such as time wasted, health problems, pollution, traffic accidents, and economic progress. According to this paradigm, individuals can rely on traffic control technologies to reduce traffic and its consequences. We may utilise a smart traffic management system that considers both the flow of traffic and the issues that individuals are facing to counteract this effect. To minimise the amount of time spent at traffic signals, identify unoccupied spaces, and stop traffic, this system concentrates on them. The examination of the procedure is described in the publication, along with the system's outcome. Recently, research has focused on using image processing technology to improve traffic problems and increase the intelligence of traffic signal controllers.
Keywords: OpenCV; Raspberry Pi; Signal Controllers; image processing; traffic management